Analiza zaznavanja dejavnikov zadovoljstva slovenskih turističnih vodnikov in spremljevalcev - Gorenak, Mitja (Naše gospodarstvo, 2011)
In this article, the author examines various job satisfaction theories and applies this theoretical knowledge to tour guides and tour managers, presuming that due to the specifics of the work and work environment, this group will present special factors that influence job satisfaction. Furthermore, the author analyses a survey conducted among 235 interviewees, representing 14.25 percent of the entire population. In the analysis, the author confirmed hypothesis that job satisfaction of tour guides and tour managers is influenced by atypical factors; the most influential factors found in this survey are ethics and professionalism within organizations, reverse apprising, work space, discipline, potential for competency development, potential for creative work, and job challenges.
Keywords: tourism; turizem; zaposleni; turistični vodiči; zadovoljstvo; delo; labour